Optically stitched arbitrary fan-sectors with selective polarization states for dynamic manipulation of surface plasmon polaritons - Guo, L. J. (2014)
Novel hybrid-polarized vector beams with radial and azimuthal polarization states in arbitrary fan-sectors are generated and studied for manipulating surface plasmon polaritons (SPPs). The method has high energy conversion efficiency based on an interferometric arrangement with a Dammann vortex phase grating. The polarization states of generated beams are measured by a linear polarizer and show excellent agreement with theoretical predictions. The manipulation properties of the hybrid-polarized beams on SPPs excitation and distribution are demonstrated by both experiments and simulations. The results show that focusing or standing wave patterns of SPPs can be obtained depending on the polarization of the beams.